Does good critical thinking equal effective decision-making among critical care nurses? A cross-sectional survey - Mohamed Ludin, Salizar (Churchill Livingstone, 2018)
Background A critical thinker may not necessarily be a good decision-maker, but critical care nurses are expected to utilise outstanding critical thinking skills in making complex clinical judgements. Studies have shown that critical care nurses’ decisions focus mainly on doing rather than reflecting. To date, the link between critical care nurses’ critical thinking and decision-making have not been examined closely in Malaysia. Aim To understand whether critical care nurses’ critical thinking disposition affects their clinical decision-making skills. Method This was a cross-sectional study in which Malay and English translations of the Short Form-Critical Thinking Disposition Inventory-Chinese Version (SF-CTDI-CV) and the Clinical Decision-making Nursing Scale (CDMNS) were used to collect data from 113 nurses working in seven critical care units of a tertiary hospital on the east coast of Malaysia. Participants were recruited through purposive sampling in October 2015. Results Critical care nurses perceived both their critical thinking disposition and decision-making skills to be high, with a total score of 71.5 and a mean of 48.55 for the SF-CTDI-CV, and a total score of 161 and a mean of 119.77 for the CDMNS. One-way ANOVA test results showed that while age, gender, ethnicity, education level and working experience factors significantly impacted critical thinking (p < 0.05), only age and working experience significantly impacted clinical decision-making (p < 0.05). Pearson’s correlation analysis showed a strong and positive relationship between critical care nurses’ critical thinking and clinical decision-making (r = 0.637, p = 0.001). Conclusion While this small-scale study has shown a relationship exists between critical care nurses’ critical thinking disposition and clinical decision-making in one hospital, further investigation using the same measurement tools is needed into this relationship in diverse clinical contexts and with greater numbers of participants. Critical care nurses’ perceived high level of critical thinking and decision-making also needs further investigation.